Trendi pri razvoju alternativnih pogonskih rešitev za gospodarska vozila - Paušer, Boštjan (Trajnost, 2025)
Concern for reducing exhaust emissions from commercial vehicles began with the first environmental regulations (Euro standards) at the end of the 1980s. Their tightening was also followed by technology and technological progress of vehicle manufacturers in engines and the development of solutions for exhaust gas aftertreatment, resulting in a more than 90 percent reduction in permitted emissions to date. In parallel, alternative propulsion solutions have also appeared in recent years, from gas in various forms to electricity and hydrogen, most of which are not new, as they were developed many years ago, but at that time, due to their high price and certain restrictions on everyday use that they entail, they did not become established. Today, we can conclude that most technologies have advanced and are also commercially available on the market, but there are still restrictions on mass use - mostly in the form of high prices and lack of infrastructure, which is why sales figures are very modest and do not follow the goals set by policy.
Keywords: alternativni pogoni; baterije; elektro mobilnost; transport; vodik